An approach towards the restoration of a critically endangered tree species in Bangladesh - regeneration of Anisoptera scaphula - Hossain, Md. Aktar; Ferdous, Jebin; M. Abdur Rahman,; Ab Shukor, Nor Aini; Azad, Md. Abul Kalam (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Anisoptera scaphula is a critically endangered tree species in Bangladesh due to poor natural regeneration. The study was conducted to explore the appropriate regeneration technique for A. scaphula through seed germination and clonal propagation by stem cutting. The effects of dewinging, seed orientation and sowing position on germination and seedling growth attributes were determined by sowing winged or dewinged seeds in control, vertical, horizontal or inverted orientation in full or half buried position. The rooting ability of one node cutting was investigated by treating with 0, 0.2, 0.4 or 0.8 % indole-3-butyric acid (IBA) solution in a non-mist propagator. The earliest germination was observed in dewinged seeds sown invertedly in the half buried sample while delayed germination occurred in the control.